2016
DOI: 10.4238/gmr.15038492
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p38-mitogen-activated protein kinase contributes to ischemia reperfusion in rat brain

Abstract: ABSTRACT. Inflammation plays an important role in cerebral ischemia reperfusion, which can cause severe damage to the brain and may lead to cerebral hemorrhage transformation. p38-mitogen-activated protein kinase (p38mapk) has been implicated in the etiology of a number of diseases because it is a cause of inflammation, but comparatively little research has been carried out into its role in the etiology of ischemia reperfusion. We investigated the expression of p38mapk in cerebral ischemia reperfusion to gain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…The p-p38 MAPK signaling pathway has been implicated in the etiology of various diseases, and it plays an important role in ischemic stroke. 29 One basic study showed that occludin, a major component of the BBB, was regulated by p38 MAPK. 30 Moreover, increasing evidence has proven that p38 MAPK is a critical signal transduction pathway involved in changes in ICH and subarachnoid hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The p-p38 MAPK signaling pathway has been implicated in the etiology of various diseases, and it plays an important role in ischemic stroke. 29 One basic study showed that occludin, a major component of the BBB, was regulated by p38 MAPK. 30 Moreover, increasing evidence has proven that p38 MAPK is a critical signal transduction pathway involved in changes in ICH and subarachnoid hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, BBB disruption after ICH may have resulted from excessive p‐p38 MAPK and AQP4 overexpression. The p‐p38 MAPK signaling pathway has been implicated in the etiology of various diseases, and it plays an important role in ischemic stroke . One basic study showed that occludin, a major component of the BBB, was regulated by p38 MAPK .…”
Section: Discussionmentioning
confidence: 99%
“…4 Neuroinflammatory mechanism and related factors of BBB ischemic stroke injury the potential NOTCH3/NF-κB signaling pathway. The mitogen-activated protein kinase (MAPK) signaling pathway also plays a crucial role in ischemic strokes [83][84][85]. P38 MAPK regulates the synthesis of occludin proteins in the BBB structure [86].…”
Section: Bbb Injuries After Ischemic Strokementioning
confidence: 99%
“…In the early stage of stroke, activation of the p38 signaling pathway promotes Elk1, C/EBP homologous protein (CHOP10), leukocyte cell-derived chemotaxin-2 (LEF2C), and protein kinases MAPKK2/3 to maintain neuronal survival and play roles in anti-inflammatory and anti-apoptotic processes. In contrast, in the late stage of stroke, p38 MAPK is overactivated and promotes the expression of target genes activating transcription factors and caspases ( 106 108 ), promoting neuronal apoptosis; thus, differences in IS p38 MAPK signal molecules should be given different interventions. This viewpoint has been supported by relevant studies showing that rhizoma coptidis jiedu soup causes overactivation of ERK and inhibition of JNK, as well as that p38 MAPK signal induction protection autophagy is beneficial for treating IS.…”
Section: Autophagymentioning
confidence: 99%